PROFIT GROWTH REVIEW FROM THE FINANCIAL PERFORMANCE ANALYSIS AND INFLATION RATE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATION - Yunus Harjito; Elizabeth Afinka Bunga Pratiwi; Sugiarti Sugiarti (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
Profit growth is one of indicators used by stakeholders to know the company’s financial performance. The high-profit growth represents that financial performance is well. Addition to internal conditions, profit growth also influenced by external conditions, such as inflation rate. The emergence of the obligation to disclose Sustainability Reporting including Corporate Social Responsibility affects financial performance and profit growth. This research intended to analyse the influence of financial performance and inflation rate on profit growth moderated by Corporate Social Responsibility disclosure. Financial performance was measured by using Net Provit Margin, Return On Equity, Quick Ratio, and Debt to Equity Ratio. The population is manufacture companies listed on the Indonesia Stock Exchange during the period from 2017-2019. A total sample of 101 companies obtained for 3 years is resulted in 303 samples by using purposive sampling as the research method. The data analysis technique used moderating regression analysis with SPSS. The research showed that Quick Ratio has a negative effect on profit growth while Debt to Equity Ratio has a positive effect on profit growth, whereas Net Provit Margin and Return On Equity did not. Therefore, the result of moderating analysis saw that Corporate Social Responsibility could moderate the effect of Quick Ratio and Debt to Equity Ratio on profit growth, but it could not moderate the effect of Net Provit Margin and Debt to Equity Ratio to profit growth.